Efficacy of an extensively hydrolyzed formula with the addition of synbiotics in infants with cow's milk protein allergy: a real-world evidence study - Soria, Ramiro; Del Compare, Mónica; Sallaberry, Marisa; Martín, Graciela; Aprigliano, Gustavo; Hermida, Verónica; Carosella, Mabel; Gruenberg, Martín; Monsell, Silvana; Micone, Paula; Maciero, Eugenia; Giglio, Norberto (Frontiers in Allergy, 2023)
Introduction Cow's milk protein allergy (CMPA) is the most frequent food allergy in early childhood. For those infants requiring breastmilk substitutes, formulas with extensively hydrolyzed proteins (EHF), should be the treatment of choice. As there are limited data showing the progression of initial symptoms in infants newly diagnosed with CMPA who are treated with EHF with added synbiotics, the main objective of this study was to evaluate the resolution of symptoms in said infants after 4 weeks of treatment. As a secondary objective this study aimed to assess the impact of the treatment on the family's quality of life. Materials and Methods observational, longitudinal, prospective, and multicentric real-world evidence study. The intervention phase (EHF with synbiotics) lasted 28 days and was completed by 65 patients. Treating physicians registered child´s anthropometry, Infant Gastrointestinal Symptoms Questionnaire (IGSQ-13) and CoMiSS (Cow´s Milk Allergy Symptoms Score) both at baseline and after 28 days of treatment. During treatment, caregivers reported child´s regurgitation and stools, PO-SCORAD (Patient Oriented Scoring of Atopic Dermatitis) and FAQL-PB (Family Quality of Life—Parental Burden). Data were collected using Google Forms and analyzed through the STATA program. Results 95.4% of the patients showed an improvement or disappearance of the overall initial symptoms after 4 weeks of treatment. Gastrointestinal symptoms improved or disappeared in 92% of patients (p < 0.05) while dermatological symptoms improved or disappeared in 87.5% of patients (p < 0.05). The median CoMiSS at baseline was 9, with 21 patients exceeding the cut-off point of 12. After 4 weeks of treatment, the median dropped to 3, and no patient exceeded the 12-cut-off point (p = 0.000). At baseline, patients had a PO-SCORAD of 11.5 (interquartile range 1–23) that went to 1.0 (interquartile range 1–6) at day 28 (p = 0.000). The treatment diminished stool frequency (p < 0.05), improved stool consistency (p = 0.004) and decreased the frequency of regurgitation in infants with CMPA (p = 0.01). The percentage of patients who no longer had any episode of regurgitation increased from 11% to 31% on day 28 (p = 0.003). At baseline, 13% of patients cried more than 3 h per day, while at day 28 that percentage dropped to 3% (p = 0.03). An improvement in the infants' sleep pattern was also appreciated with the treatment. At study onset, 56% of the families reported feeling very overwhelmed, a percentage that dropped to 17% after 28 days of treatment (p < 0.05). The small percentage of families who did not feel overwhelmed at study onset (17%), grew to 43% on day 28 (p < 0.05). Conclusions The use of an EHF with synbiotics for the management of infants diagnosed with or suspected to have CMPA suggested a good safety profile, an adequate infant growth, and improvement of overall, gastrointestinal, and dermatological symptoms. It also suggested a lower daily frequency of regurgitations and stools, and an improvement in stool consistency, sleeping pattern, and quality of life of the infant and his family.